1994
DOI: 10.1093/oxfordjournals.jbchem.a124343
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrophilic Tetrahydro-β-Carboline in Human Urine

Abstract: A substance that exhibited a tryptophan-like fluorescence peak at 354 nm on excitation at 295 nm at neutral pH was isolated from human urine. This compound was determined by visible-light absorption spectroscopy, fluorescence spectroscopy, 1H and 13C NMR spectroscopies, and FAB-MS to be 1-(1',2',3',4',5'-pentahydroxypentyl)-1,2,3,4-tetrahydro-2-carboli ne-3- carboxylic acid. This compound, named tetrahydropentoxyline, is a new type of hydrophilic tetrahydro-beta-carboline, and its elution position was between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…The chemical shifts and coupling constants of compound 1 correspond to reported results [7], but the topological assignments of the "$C-NMR signals are different. In the "H-NMR spectrum of compound 1, the signal of the indole H-2 is absent, indicating that tryptophan is substituted at C-2 by the hexose moiety (indole H-1 was not observable owing to proton exchange in the applied solvents C#H $ O#H and #H # O).…”
Section: Figure 8 Section Of the One-dimensional Nmr Spectrum Of 2-(αsupporting
confidence: 82%
See 1 more Smart Citation
“…The chemical shifts and coupling constants of compound 1 correspond to reported results [7], but the topological assignments of the "$C-NMR signals are different. In the "H-NMR spectrum of compound 1, the signal of the indole H-2 is absent, indicating that tryptophan is substituted at C-2 by the hexose moiety (indole H-1 was not observable owing to proton exchange in the applied solvents C#H $ O#H and #H # O).…”
Section: Figure 8 Section Of the One-dimensional Nmr Spectrum Of 2-(αsupporting
confidence: 82%
“…This compound was proposed to have a tetrahydro-β-carboline structure, but the identity of the sugar part remained to be established [7]. As the occurrence of related tryptophan glycoconjugates in dietary sources has not yet been investigated, an exogenous origin for the tryptophan metabolite could not be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of MPT is illustrated in Figure 1. MPT is found in serum and cerebrospinal fluid [2]. Although its metabolism and physiologic role remain to be clarified, our previous report has shown that MPT clearance is almost identical to inulin clearance in experimental animals, indicating a similar renal handling of the two molecules [4].…”
mentioning
confidence: 98%
“…Serum creatinine concentration is widely used for assessing renal function in the clinical setting, because of its speed and simplicity. However, as it is greatly influenced by muscle mass as well as renal function [1][2][3], the measurement of serum creatinine concentration can be prone to misinterpretation of the results in subjects with diminished muscle mass, such as the elderly, children, and females. Thus, the measurement of serum creatinine concentration may overestimate renal function in these populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation